The influence of road traffic and industrial plant-induced air pollution on the physical, mechanical, chemical and morphological properties of the black pine wood - Koksal, Suheyla Esin; Kelleci, Orhan; Tekingunduz, Gul; Aydemir, Deniz (Maderas. Ciencia y Tecnología, 2024)
Road traffic pollution and industrial plant-induced pollution affect negatively the development of forest trees. How forest trees are affected by their growing environment is important for sustainable environment. The study aimed to investigate the physical, mechanical, chemical, and morphological properties of the Pinus nigra (black pine) tree which grows under different conditions. Tree samples were chosen from three different lands where were inside the forest (O), near the roadside (Y), and near the factory (F). It was studied whether there were any significant differences among the “O”, “Y” and “F” in terms of their wood properties such as physical, mechanical, chemical, and morphological. As a result, the “O” samples demonstrated more regular annual ring structure. On the other hand, it was observed that the “Y” samples had longer and wider tracheid cells. In addition, “Y” samples had better mechanical strength than “O” and “F”. Environmental pollution caused the presence of some different elements (chlorine and iron) in “Y” and “F”. As a result, it was determined that the trees growing near the roadside or near industrial plants have significant differences from forest trees which are far away from pollutions. It is possible to say that Pinus nigra (black pine) is resistant to environmental stress. For this reason, it can be recommended to use it as a barrier to reduce air pollution on the roadsides.